2020
DOI: 10.1111/jora.12592
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Links between Adolescent and Peer Conduct Problems and Moderation by a Sensitivity Genetic Index

Abstract: The most extensively studied influence on adolescent conduct problem behaviors is peers, and the literature points to genetics as one source of individual differences in peer influence. The purpose of this study was to test the hypothesis that an environmental sensitivity genetic index comprised of DRD4, 5‐HTTLPR, and GABRA2 variation would moderate the association between peer and adolescent conduct problems. Latent growth modeling was applied to PROSPER project longitudinal data from adolescents and their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…4). A recent study of 11 000 individuals confirmed GABRA2 as a genetic plasticity factor with regard to behavioural outcomes (Schlomer 2020), whereas GWAS of alcoholism or alcohol intake (Gelernter 2019;Kranzler 2019) did not identify GABRA2 as a risk variant. The molecular mechanism is still not understood as the plasticity allele of GABRA2 is a haplotype involving >200 SNPs (Enoch 2008), none of them known to be functional.…”
Section: Fkbp5 Encoding Fk506-binding Protein 51mentioning
confidence: 99%
“…4). A recent study of 11 000 individuals confirmed GABRA2 as a genetic plasticity factor with regard to behavioural outcomes (Schlomer 2020), whereas GWAS of alcoholism or alcohol intake (Gelernter 2019;Kranzler 2019) did not identify GABRA2 as a risk variant. The molecular mechanism is still not understood as the plasticity allele of GABRA2 is a haplotype involving >200 SNPs (Enoch 2008), none of them known to be functional.…”
Section: Fkbp5 Encoding Fk506-binding Protein 51mentioning
confidence: 99%
“…Especially important is that this is so when diverse environmental indices (e.g., parenting, neighborhood violence, SES, father absence) are used as predictors, with markers of reproductive strategy, the outcome to be explained, including opportunisticexploitative behavior (Brody et al, 2011;Davies et al, 2019;Fine et al, 2016;Gibbons et al, 2012;Rogosch & Cicchetti, 2013;Schlomer et al, 2021;Simons et al, 2011) and pubertal timing (Hartman et al, 2015;Manuck et al, 2011;Schlomer & Cho, 2017;Schlomer & Marceau, 2020;Sun et al, 2020). Unfortunately, to my knowledge, there is no such differential-susceptibility-related work focused on age of sexual debut or first birth, unstable partner relationships or number of children born.…”
Section: Differential Susceptibilitymentioning
confidence: 99%